2018
DOI: 10.29011/2576-9596.100037
|View full text |Cite
|
Sign up to set email alerts
|

The Meniscus and Meniscal Scaffolds for Partial Meniscal Replacements

Abstract: The meniscus is the most common damaged structure of the knee, accounting for almost one million cases of knee surgeries performed annually in the United States alone. A complete meniscectomy (complete meniscus removal) was the most common procedure performed in 1889 and was the standard procedure in the next 80 years. However, follow-up radiographic studies from the late 1960s to 1980s reported a high frequency of post-meniscectomy osteoarthritis of the knee.The meniscus functions to transmit load, absorb sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The mechanical properties of the scaffolds vary when the tests are conducted with dry or wet samples. Data obtained with wet scaffolds are more similar to those of the native meniscus than those obtained with dry scaffolds because the microenvironment of the meniscus is aqueous and reorganizes under stress . The mechanical evaluation of hydrated samples confirmed that the composite scaffolds were structural units because they retained their integrity until reaching the breaking point in the test.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of the scaffolds vary when the tests are conducted with dry or wet samples. Data obtained with wet scaffolds are more similar to those of the native meniscus than those obtained with dry scaffolds because the microenvironment of the meniscus is aqueous and reorganizes under stress . The mechanical evaluation of hydrated samples confirmed that the composite scaffolds were structural units because they retained their integrity until reaching the breaking point in the test.…”
Section: Discussionmentioning
confidence: 99%